Hedge funds and the positive idiosyncratic volatility effect - Turan G. Bali; Florian Weigert (University of Cologne, Centre for Financial Research (CFR), 2021)
While it is established that idiosyncratic volatility has a negative impact on the cross-section of future stock returns, the relationship between idiosyncratic volatility and future hedge fund returns is largely unexplored. We document that hedge funds with high idiosyncratic volatility outperform and this pattern is explained by the positive return effect of idiosyncratic volatility in their equity portfolio holdings. Hedge funds select stocks wisely by picking high-volatility stocks when they are undervalued and shying away from high-volatility stocks when they are overvalued or display lottery-like payoffs. They also trade derivatives in a way to profit from the positive volatility effect.
Keywords: G11; G23; 330; Hedge Funds; Idiosyncratic Volatility Puzzle; Equity Portfolio Holdings; Derivatives; Managerial Incentives; Investment Performance